BUMDesa Management Model Based on Regulation and Local Wisdom - Putra, Permata Kardina (Future Science, 2025)
This research aims to analyze the regulation-based BUMDesa management model, namely the conformity of BUMDesa management with Government Regulation Number 11 of 2021 and the local wisdom values ​​that contribute to the development of BUMDesa. This qualitative descriptive research uses primary data obtained through interviews and observation. The research results show that BUMDesa management can be used as an example because regulatory aspects and local wisdom values ​​contribute to the development of BUMDesa. Local wisdom in the community is able to encourage the role of village communities in advancing BUMDesa businesses. The key to success in managing BUMDesa is the implementation of the vision and mission through the unity of the BUMDesa management whose foundation is not for personal interests but through the philosophy of sincere, intelligent work which is an important aspect in maintaining the trust of the community. The management of BUMDesa is assessed by the community as one of the factors due to morals, loyalty and cooperation in developing BUMDesa. public.